Laboraturium IPA sebagai sumber belajar mahasiswa PGMI IAIN Langsa - Iqbal, Muhammad; Junaidi, Junaidi (azkiya, 2023)
The efforts of the PGMI Study Program to improve the quality of its students by providing Science Lab facilities (Science Lab) are not in line with the conditions in the field which show that there are still many practicum tools in the Science Lab that are not available as they should. The purpose of this study is to determine the management techniques of Science Lab as one of the learning resources for students of PGMI Study Program IAIN Langsa, to find out the dominant factors that influence the utilization of Science Lab PGMI Study Program IAIN Langsa and the obstacles faced in carrying out teaching and learning process activities in Science Lab PGMI Study Program IAIN Langsa. The type of research is a qualitative survey while the research subject is done by purposeful sampling method, with data collection techniques namely observation, interview, and documentation. The results showed that the Head of the Science Lab in carrying out his duties formulated an operational schedule for using the Lab, while the factors that can affect the utilization of the Science Lab are the lack of practicum tools and materials, besides that the student knowledge factor is still low, exacerbated by the Covid-19 Pandemic. So that the practicum process that should run in the Lab cannot run properly and optimally, while the solutions offered are; revamping practicum tools, using simple tools and materials around students, and proposing a laboratory assistant who can help lecturers to prepare the tools and materials needed in practicum.